Factors controlling the geographical distribution of fluorescent dissolved organic matter in the surface waters of the Pacific Ocean. (19th April 2017) - Yamashita, Youhei; Hashihama, Fuminori; Saito, Hiroaki; Fukuda, Hideki; Ogawa, Hiroshi
Abstract: Dissolved organic matter (DOM) in the epipelagic ocean is produced by marine organisms and consumed by microbes. Thus, the distributional patterns of DOM quantity and quality in surface waters are possibly related to marine ecological provinces. In this study, surface waters collected throughout the Pacific Ocean were used to investigate the geographical distributions of fluorescent DOM (FDOM) quantity and quality. An excitation‐emission matrix and parallel factor analysis revealed two humic‐like and two protein‐like components. The levels of humic‐like components showed clear meridional trends with some zonal variability and were highest and lowest in the northern high‐latitude and the subtropical provinces, respectively. The photochemical reactivity, determined by the ratio of two humic‐like components, was found to be lowest in the subtropical provinces, implying that the major factor controlling the geographical distribution of humic‐like components is the degree of photobleaching. The distributional patterns differed between levels of two protein‐like components, i.e., tryptophan‐like and tyrosine‐like. The ratio of tyrosine‐like to tryptophan‐like components was established as a possible indicator of microbial degradability, and the highest ratio occurred in subtropical provinces. A negative correlation was found between this ratio and the chlorophyll a concentration. Such geographical distributions of protein‐like components imply that relatively recalcitrant protein‐like components are distributed uniformly throughout the surface waters, but substantial contributions of reactive fractions occur in regions characterized by high biological production. Cluster analysis with the FDOM composition clarified that the diagenetic states of DOM were similar and variable in the northern high‐latitude and the subtropical provinces, respectively.